2017
DOI: 10.1007/s11605-017-3453-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Enteroatmospheric Fistula in Open Abdomen Treated with Negative Pressure Wound Therapy: a Multicentre Experience

Abstract: Mesenteric ischaemia increases the risk of enteroatmospheric fistulae. Anastomosis should only be created in revascularized patients. When mesenteric vascularization is not restored, diversion is advised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 27 publications
0
18
1
1
Order By: Relevance
“…In a multicenter prospective study of non‐trauma OA by Bruns et al ., 9 the rate of 6‐month mortality was 64%, which was significantly high, in patients aged ≥80 years. Another multicenter survey of non‐trauma OA revealed a 1‐year mortality of 33%, but that study included patients younger than those in our study; the mean age was 62.7 years 19 …”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In a multicenter prospective study of non‐trauma OA by Bruns et al ., 9 the rate of 6‐month mortality was 64%, which was significantly high, in patients aged ≥80 years. Another multicenter survey of non‐trauma OA revealed a 1‐year mortality of 33%, but that study included patients younger than those in our study; the mean age was 62.7 years 19 …”
Section: Discussionmentioning
confidence: 76%
“…Another multicenter survey of non-trauma OA revealed a 1-year mortality of 33%, but that study included patients younger than those in our study; the mean age was 62.7 years. 19 Some researchers have evaluated the long-term functional outcome of OA. Kriwanek et al, using the 36-item short form survey (SF-36) to evaluate long-term physical functional outcomes, interviewed surviving non-trauma patients with OA, aged 50-60 years.…”
Section: Discussionmentioning
confidence: 99%
“…In 1995, Qiu et al applied abdominal VSD for the rst time in China [3]. Later, many studies have shown that VSD is effective in controlling abdominal infection, clearing abscess and shortening healing time [4,5,6].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 26 articles were included, of which 3 were RCTs 20 , 71 , 72 and 23 were observational studies and case series. 26 , 50 , 64 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 …”
Section: Recommendationsmentioning
confidence: 99%
“…Multiple observational studies on the use of VSD for retroperitoneal space infections with different causes have shown that VSD can control early local infection, keep the abscess clean, promote collapse of the abscess, shorten healing time, reduce local complications, and reduce VSD-related complications 73, 74, 75. Tao et al 76 .…”
Section: Recommendationsmentioning
confidence: 99%